To surcharge or not to surcharge? A two-sided market perspective of the no-surchage rule - Nicholas Economides; David Henriques (European Central Bank (ECB), 2011)
In Electronic Payment Networks (EPNs) the No-Surcharge Rule (NSR) requires that merchants charge the same final good price regardless of the means of payment chosen by the customer. In this paper, we analyze a three-party model (consumers, merchants, and proprietary EPNs) to assess the impact of a NSR on the electronic payments system, in particular, on competition among EPNs, network pricing to merchants and consumers, EPNs' profits, and social welfare. We show that imposing a NSR has a number of effects. First, it softens competition among EPNs and rebalances the fee structure in favor of cardholders and to the detriment of merchants. Second, we show that the NSR is a profitable strategy for EPNs if and only if the network eect from merchants to cardholders is sufficiently weak. Third, the NSR is socially (un)desirable if the network externalities from merchants to cardholders are sufficiently weak (strong) and the merchants' market power in the goods market is sufficiently high (low). Our policy advice is that regulators should decide on whether the NSR is appropriate on a market-by-market basis instead of imposing a uniform regulation for all markets.
Keywords: L13; L42; L80; 330; American Express; Discover; Electronic payment system; market power; MasterCard; network externalities; no-surcharge rule; regulation; two-sided markets; Visa